Some characteristics of the sociometrically chosen and rejected grade six pupils - Ancheta, Milagros Fe 1928- (Quezon City, 1970)
The purpose of the study is to determine through a socio-metric instrument composed of categories namely physical, social, emotional and intellectual, the traits associated with the "chosen" and the "rejected" children, particularly, the sixth grade pupils. Results of the study may serve as guides in developing positive or desirable traits in children which may prove useful in helping the socially rejected children attain satisfactory status among the members of their group and thereby possibly ensure better achievement and proper adjustment. It can also serve as a ready sample for teachers in the use of the sociometric technique.
Thesis (M.Ed.)--University of the Philippines
Keywords: Students -- Pagadian, Zamboanga del Sur; Child study